Kebijakan Nonpenal oleh Badan Narkotika Nasional Provinsi Jambi terhadap Penyalahguna Narkotika - Reza Iswanto (Wajah Hukum, 2018)
Narcotics abuse is increasing now and many victims have fallen victim to drug abuse. Therefore, the role of the National Narcotics Board of Jambi Province is needed in overcoming the level of narcotics abuse. In conducting nonpenal policy, the National Narcotics Board of Jambi Province only conducts socialization in schools and rehabilitation only accommodates 10 drug abusers. Thus, the solution in using the nonpenal policy is the National Narcotics Board of Jambi Province should increase the socialization, make the communities of ex-narcotics abusers who have recovered to be guides against new drug abuse entrants into rehabilitation, should work together with the police to conduct raids , using the role of mass media in providing news about the dangers of drug abuse and the National Narcotics Board of Jambi Province should provide rehabilitation center for narcotics abusers. To get the solution, then used the approach of sociology of law by giving priority to primary data conducted by interview and located in National Narcotics Agency of Jambi Province.